Analisis Constructivist Multimedia Learning Environment dengan Pendekatan Bayesian Structural Equation Model - Adhistya Erna Permanasari; Eny Sukani Rahayu; Dewa Ayu Putu Nadya Hareswary; Inas Ulfah Prisabtini (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Constructivist Multimedia Learning Environment (CMLE) is a learning model where the teacher gives the student an experience that can help them to develop high order thinking skills such as critical thinking, developing solutions, and be creative around their environment. CMLE uses multimedia as their main source of information and as a tool to deliver learning materials. For that purpose, evaluation is needed to assess the effectiveness of the learning model. This evaluation is known as CMLE Survey (CMLES). Data obtained from CMLES needs to be analysed using analytical methods that can show the relationship between each variable and the indicator. Bayesian Structural Equation Model (SEM) is considered as the right approach because of many advantages of Bayesian Approach, such as using prior information to get posterior result and not affected by the number of samples. The seven existing hypotheses are accepted with the following results. RTH has a positive influence on CHL while CHL has a positive effect on COM. RLV has a positive influence on COM. RTH has a positive influence on INQ while INQ has a positive influence on NEG. Nevertheless, CHL gives a negative influence on INQ and RLV gives a negative influence on CHL.